Masyarakat Cina di selatan Vietnam dalam abad ke-17 hingga abad ke-18 / Ong Kui Hua - Ong , Kui Hua (2015)
Chinese Community in Southern Vietnam in the 17th to 18th Centuries The immigration of the Chinese to Vietnam can be traced to the Han dynasty when emperor Han Wu Ti (140BC-87BC) sent General Lu Po-te to conquer Nam Yueh (Vietnam or Nam-Viet) in the 111BC. Subsequent waves of Chinese migration to Vietnam took place whenever there was major political turbulence taking place in China. The mass migration of Chinese to southern Vietnam occured in 1644 after the fall of Ming dynasty. The migration of Chinese to southern Vietnam after the fall of Ming dynasty in 1644 had more profound effect on the historical and demographical development in southern Vietnam. This wave of migration in the 17th century coincided with the southward expansion of the Vietnamese under the Nguyen family. The new arrivals from China were accepted by the Nguyen who also began to utilize them in the process of territorial and political expansion programme. This study investigates first, the state-to-community relations between the Nguyen and the Chinese immigrants in southern Vietnam with specific focus on the policies of the Chinese and Vietnamese governments with regard to the issue of the Chinese migration to southern Vietnam. Effort will be made to examine the manner in which the Nguyen turned the new Chinese immigrants into a useful human resource in assisting the Nguyen to achieve its expansion programme in the new land of Chams and the Khmer. Secondly, this research also look into the transformation of this new Chinese community including factors which had encouraged the majority of Chinese to choose to settle in the southern Vietnam and not in the northern Vietnam. Thirdly, the relationship between the Chinese community and the local community, and how these relationship had helped to establish new hybrid communities such as the Minh Huong and Thanh Ha communities in southern Vietnam, also be studied. Another related aspect which is the focus of the study is the initiative of the Chinese community to preserve the culture of their origin and the challenges faced in this endeavour. This research is important in three fields. First, currently there is no single research that looks at the history of the Chinese in southern Vietnam in a comprehensive manner. This study is an effort to obtain a layer of events as to be able to understand the development of Vietnamese history as a whole. Secondly, this study will attempt to look beyond the conventional issues of immigration and the Chinese's role in the Vietnamese (Nguyen's)'s political expansion. It will attempt to look at the next level of Chinese presence in southern Vietnam by looking at the inter-ethnic relations between the Chinese and the Vietnamese as well as between the Chinese and the minority hill tribes. This is an area which has thus far been neglected by most scholars. Thirdly, by looking closer into the position and reaction of the Chinese in inter-ethnic relations, this study will be significant in providing new dimension to the existing historiography on the Chinese in Vietnam as well as on the history of Southeast Asia.